Comparative analysis of certain soil microbiological characteristics of the carbon cycle - Mátyás, Bence; Horváth, Judit; Kátai, János (Acta Agraria Debreceniensis, 2016)
In our researches, we examine the soil microbial parameters related to the carbon cycle. In this study, we compare the changes of microbial biomass carbon (MBC) and the soil CO2 production in soil samples which were taken in spring and autumn. The 30 years old long-term experiment of Debrecen-Látókép is continued in our experiments. The long-term fertilization experiment was set in 1983, and our sample was taken in spring 2014. The examinations of soil respiration processes and factors that influence soil respiration are required in optimal management. In our study, we interested to know how the growing levels of fertilization influence the soil respiration and microbial biomass carbon under non-irrigated and irrigated conditions in maize mono, bi, and triculture.